Meetings between experiences of being a child in São Paulo and São Gabriel da Cachoeira - Massagardi Caetano da Silva, Nadia; Santiago do Nascimeto, Ana Paula (Guará Journal, 2024)
This paper presents the actions and reflections carried out in the project “Correspondence between diff erent Brazilian chil-dhood experiences” carried out in the years 2017 and 2018 with children from 4 to 6 years of age that involved teaching, the re-search and university extension in the exchange of correspon-dence between children of São Paulo - SP and São Gabriel da Cachoeira - AM. It was carried out through circles of conversa-tions and photographic and graphic records on the daily lives of children and documentary and bibliographical surveys on indigenous communities in Brazil. This action contributed to the change of perspective of children about indigenous peo-ples and the continuing education of educators involved in the process.